Thermal Treatment in Milk Processing: Using a Complex Energy-Substitution Equipment during Preliminary Water Heating - Gerber Y.; Gavrilov A.; Verbitsky A. (Техника и технология пищевых производств)
Energy input affects the final cost of dairy products. The paper features energy cost optimization in dairy industry and, in particular, in the production of cultured milk foods. The present research studies the options for renewable energy sources in dairy industry: solar system is becoming a very promising means of energy saving in the southern regions. The authors proposed a complex energy substitution device, which can reduce the electricity costs by 60–70%, according to preliminary calculations. The results obtained in the theoretical underpinning of design parameters and operation modes were checked by experimental studies. For the experiment, the authors designed and manufactured a water heating system based on flat solar collectors. An instrument complex registered temperature values in eight different control points and transferred the signals to a PC hard disk. The article presents the parameters of the equipment in pasteurization and milk fermentation processes with the use of the complex energy substitution device for water heating. The equipment can be used by large-scale dairy enterprises, since the area of the collectors for the preliminary water heating is 2 m2, which provides 150 litters of water with a temperature of 45–60°C. As the normative parameters of the temperature during the milk fermentation process is 32–35°C, and the water temperature in the device is 45–60°C, it can be concluded that the thermal costs are fully covered.